Pemberdayaan Masyarakat Berbasis Pendekatan Partisipatif Melalui Program Kuliah Kerja Nyata Universitas Negeri Padang di Nagari Sikucur, Kabupaten Padang Pariaman - Rahmania Amanda Asri; Wizi Wulandari; Evi Afrina Susanti; Rizqi Putra Pelani; Novita Efendi (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a community engagement program organized by Universitas Negeri Padang as an implementation of the Tri Dharma of Higher Education. This program was conducted in Nagari Sikucur, V Koto Kampung Dalam District, Padang Pariaman Regency, West Sumatra Province, from January 9 to February 9, 2026. The program aimed to empower the local community through a participatory approach based on the identification of local needs and potentials. The methods applied consisted of several stages, including observation, planning, implementation, evaluation, and reporting, while actively involving community members in every activity. The implemented programs covered several areas, such as education and religious development, social and psychosocial activities, as well as economic empowerment and strengthening of village physical facilities. The results of the activities indicated an increase in community participation, the strengthening of religious values and social solidarity, and support for the development of local economic potential. Despite several challenges, including limited implementation time and adjustments to program targets, the collaborative approach proved effective in encouraging community engagement. Therefore, the KKN program of Universitas Negeri Padang in Nagari Sikucur contributed positively to strengthening the social, religious, and economic capacities of the local community.